2009
DOI: 10.1007/s10753-009-9118-2
|View full text |Cite
|
Sign up to set email alerts
|

IFN-Gamma and IL-4 in Saliva of Patients with Oral Lichen Planus: A Study in an Ethnic Chinese Population

Abstract: Interferon-gamma (IFN-gamma) and interleukin-4 (IL-4) represent T helper 1 (Th1) and T helper 2 (Th2) cytokines involved in oral lichen planus (OLP), respectively. This study was to investigate the expression profile of IFN-gamma and IL-4 in saliva of OLP patients. Seventy-nine ethnic Chinese patients with OLP were recruited for this study, together with 41 age-sex-matched healthy volunteers served as control group. IFN-gamma and IL-4 levels in whole unstimulated saliva were screened by enzyme linked immunosor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 33 publications
5
32
1
1
Order By: Relevance
“…IL-18 plays a crucial role in the regulation of Th1 cell differentiation, which induces pro-inflammatory cytokine and chemokine production, such as TNF-α, IFN-γ, and GM-CSF, and upregulates both the FasLand perforin-dependent cytotoxic effector functions of T and NK cells. It has been suggested that OLP is largely a Th1-polarized immune response, where CD8 + cellmediated cytotoxicity causes severe tissue damage [9,23]. The assays have shown that an elevated IL-18 expression was detected in the serum of OLP-affected patients in the study, correlating with the disease progression.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…IL-18 plays a crucial role in the regulation of Th1 cell differentiation, which induces pro-inflammatory cytokine and chemokine production, such as TNF-α, IFN-γ, and GM-CSF, and upregulates both the FasLand perforin-dependent cytotoxic effector functions of T and NK cells. It has been suggested that OLP is largely a Th1-polarized immune response, where CD8 + cellmediated cytotoxicity causes severe tissue damage [9,23]. The assays have shown that an elevated IL-18 expression was detected in the serum of OLP-affected patients in the study, correlating with the disease progression.…”
Section: Discussionmentioning
confidence: 69%
“…In our previous study, the profile of some proinflammatory cytokines such as IFN-γ, TNF-α, IL-4, IL-6, and IL-8 can be elevated to various degrees in OLP patients [9,10]. Recent evidence also suggests that IL-18 is a cytokine relevant in the pathogenesis of OLP.…”
Section: Introductionmentioning
confidence: 82%
“…As there was a close relationship between Th1/Th2 (T helper type 2) imbalance and pathogenesis of autoimmune diseases including Behcet's disease (Th1 dominant response) [17] and Sjögren syndrome (Th2 dominant response) [18], several recent studies have shown that Th1/Th2 imbalance also plays an important role in OLP pathogenesis [19,20]. Th1 cells primarily secrete interleukin 2 (IL-2), IL-12 and IFN-g. A recent study reported IL-12p40 and IFN-g proteins were significantly upregulated in OLP [21].…”
Section: Discussionmentioning
confidence: 99%
“…A series of inflammation-and immune regulation-related cytokines, such as interferon-gamma (IFN-γ) and interleukin-4 (IL-4), TNF-alpha (TNF-α) and IL-10, and IL-8, which have an important role in the pathogenesis and disease progression of OLP, have been investigated for establishing the connection to gene polymorphisms with OLP in the Chinese population. These studies have identified that genetic variants were a positive influence on disease susceptibility and on the progression of OLP (Bai et al, 2009;Liu et al, 2009;Dan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%